Ground Contact Detection with Shortstroke Buttons for Biped Robots. Issue 1 (December 2013) - Ewald, Alexander; Beutler, Fabian; Buschmann, Thomas
Abstract Robust walking motion of humanoid robots requires a sensor system that can accurately sense the robot's state and its environment. Especially in case the ground is not modeled and uneven, information about the contact state is crucial to initiate an appropriate response. Many humanoid robots use strain gauge‐based force/torque sensors to obtain information about the contact state. In this paper, we propose the integration of shortstroke buttons in the foot design to detect ground contact faster and more reliably. Simulation results with our robot Lola suggest that impact forces in case of an unexpected ground contact can be reduced significantly by integrating these sensors. (© 2013 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)